2009
DOI: 10.1111/j.1749-6632.2009.04756.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐B27 and HLA‐B51 Determination in Tunisian Healthy Subjects and Patients with Suspected Ankylosing Spondylitis and Behçet's Disease

Abstract: The aim of this retrospective study is to assess the frequency of HLA-B27 and HLA-B51 in healthy subjects from the center of Tunisia and to investigate their usefulness in the diagnosis of ankylosing spondylitis (AS) and Behçet's disease (BD), respectively. Microlymphocytotoxicity test was used to perform serologic HLA typing in a group of 124 healthy volunteers and a group of 365 patients suffering from clinical manifestations of AS and/or BD. HLA-B27 was found in 3.2% of healthy subjects and in 42.9% of pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…A study on 100 AS Algerian patients reported a frequency of 63% (Amroun et al., ). Equivalent HLA‐B27 frequencies have been described in the North African countries: Egypt (59% (Tayel et al., )), Morocco (58% (Atouf et al., )) and Tunisia (43%, Sakly et al., ). Various ancestral genetic components in the northern Africa have been described because of a complex history of demographic events (Bekada et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…A study on 100 AS Algerian patients reported a frequency of 63% (Amroun et al., ). Equivalent HLA‐B27 frequencies have been described in the North African countries: Egypt (59% (Tayel et al., )), Morocco (58% (Atouf et al., )) and Tunisia (43%, Sakly et al., ). Various ancestral genetic components in the northern Africa have been described because of a complex history of demographic events (Bekada et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…10,15,16 our case report is the first observation of coexistence of these diseases. Chance occurrence of these two rare diseases in the same patient, who also has HLA-B27 positive ankylosing spondylitis, had not been reported.…”
Section: Discussionmentioning
confidence: 58%
“…Such incredible predominance of the disease is also related with HLA-B51 which is almost present in 60 to 70% of BD patients from the previous mentioned areas, 9 the frequency of HLA-B51 in Tunisian patient with BD was 30%. 10 Besides, many non-HLA genes along with environmental factors contribute to the increasing risk of the disease. Some researches have revealed that MEFV gene is one of vulnerable genes which are liable to yield BD, mainly for patients with vascular involvement, in France 11 and Turkey 12 and Israel, 13 where BD and FMF are prevalent.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of the HLA-B51 antigen in ethnic groups varies from 0% to more than 25%. Populations with a high HLA-B51 prevalence (> 10%) are predominantly located in the Middle East, Greece, Turkey, Iran, and Japan [15]. While B51 is identified in an average of 15–20% of the healthy population in Turkey, in BD this ratio increased to 50–60%.…”
Section: Discussionmentioning
confidence: 99%